Perspektywy zastosowań metod Krytycznej Analizy Dyskursu w badaniach nad prawem : kilka uwag - Sulikowski, Adam (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
The purpose of this paper is to present the origins and methodological specificity of Critical Discourse Analysis (CDA) and the prospects for its application in the context of jurisprudence. The paper’s starting point is a discussion of the chain of intertextual connections that has conditioned the development of discourse analyses, from structural inquiries to criticism in the spirit of the Frankfurt School. In addition, the article briefly describes the CDA research approach according to N. Fairclough and the aims of CDA according to T.A. van Dijk. The section devoted to the prospects for applying Critical Discourse Analysis to jurisprudence includes an analysis of the advantages, but also the necessary transformations of CDA in the context of a variety of studies within jurisprudence.
Keywords: Critical Discourse Analysis (CAD)